Role of Dietary Salt and Potassium Intake in Cardiovascular Health and Disease: A Review of the Evidence - Aaron, Kristal J. (2013)
The objective of this review is to provide a synthesis of the evidence on the effect of dietary salt and potassium intake on population blood pressure, cardiovascular disease, and mortality. Dietary guidelines and recommendations are outlined, current controversies regarding the evidence are discussed, and recommendations are made based on the evidence. Designed search strategies were used to search various databases for available studies. Randomized trials of the effect of dietary salt reduction and/or increased potassium intake on blood pressure, target organ damage, cardiovascular disease, and mortality were included. Fifty-two publications from January 1, 1990 to January 31, 2013 were identified for inclusion. Evidence from these studies demonstrate that a high salt intake not only increases blood pressure but also plays a role in endothelial dysfunction, cardiovascular structure and function, albuminuria and kidney disease progression, and cardiovascular morbidity and mortality in the general population. Conversely, dietary potassium attenuates these effects showing a linkage to reduction in stroke rates and cardiovascular disease risk. Various sub-populations, such as overweight and obese individuals and the aging adult, exhibit a greater sensitivity to the effects of reduced salt intake and may gain the most benefits. A diet that includes modest salt restriction while increasing potassium intake serves as a strategy to prevent and/or control hypertension and decrease cardiovascular morbidity and mortality. Thus, the body of evidence supports population-wide sodium reduction and recommended increases in dietary potassium as outlined by current guidelines as an essential public health effort to prevent kidney disease, stroke, and cardiovascular disease.